2015
DOI: 10.1093/brain/awv336
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of intentional harm in the human amygdala

Abstract: A decisive element of moral cognition is the detection of harm and its assessment as intentional or unintentional. Moral cognition engages brain networks supporting mentalizing, intentionality, empathic concern and evaluation. These networks rely on the amygdala as a critical hub, likely through frontotemporal connections indexing stimulus salience. We assessed inferences about perceived harm using a paradigm validated through functional magnetic resonance imaging, eye-tracking and electroencephalogram recordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
77
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 29 publications
7
77
0
2
Order By: Relevance
“…Likewise, Sato et al (2011) showed greater gamma-band activity in response to fear compared to neutral faces between 50 and 150 ms. Even though this study confirmed early responses to emotional stimuli, sensory or attentional unawareness was not manipulated and stimuli were projected centrally for 1 s. Similarly, Hesse et al (2016) recorded local field potential in three patients with depth electrodes placed in the Amg and found that early activity in Amg (80–200 ms), but not in other temporal, parietal, or frontal sites, predicts rapid encoding of intentional harm from visual scenes (Hesse et al, 2016). Lastly, a recent study by Mendez-Bertolo et al (2016) found fast Amg responses beginning 74 ms post-stimulus onset specific for fearful compared to neutral or happy facial expressions.…”
Section: Timing Of Amg Response: Fast Signals For Slow Measures?mentioning
confidence: 67%
“…Likewise, Sato et al (2011) showed greater gamma-band activity in response to fear compared to neutral faces between 50 and 150 ms. Even though this study confirmed early responses to emotional stimuli, sensory or attentional unawareness was not manipulated and stimuli were projected centrally for 1 s. Similarly, Hesse et al (2016) recorded local field potential in three patients with depth electrodes placed in the Amg and found that early activity in Amg (80–200 ms), but not in other temporal, parietal, or frontal sites, predicts rapid encoding of intentional harm from visual scenes (Hesse et al, 2016). Lastly, a recent study by Mendez-Bertolo et al (2016) found fast Amg responses beginning 74 ms post-stimulus onset specific for fearful compared to neutral or happy facial expressions.…”
Section: Timing Of Amg Response: Fast Signals For Slow Measures?mentioning
confidence: 67%
“…A unique approach to define necessary hubs in brain networks and infer reliable mechanisms in cognitive neuroscience consists in applying direct intracranial electrical stimulation to single subjects (epilepsy patients implanted with depth electrodes) in specific brain regions to causally modulated cognitive task performance. Here, as part of an ongoing program of research (Chennu et al, 2013; Canales-Johnson et al, 2015; Hesse et al, 2016), we profited from the unique opportunity to produce such causal evidence via single-subject direct intracranial electrical stimulation (Parvizi et al, 2012; Mégevand et al, 2014). Specifically, we stimulated the left parietal cortex (precuneus) during the visual STM task in a patient implanted with intracranial electrodes, and compared the results with a non-stimulated condition and to the performance of a matched control group (for details about the participant and the controls, see “Participants” Section; intracranial recording specifications are offered in “Subject’s Intracranial Recording” Section).…”
Section: Working Memory Binding: Antecedents and Case Reportmentioning
confidence: 99%
“…Emotion-processing deficits have been associated with moral judgment impairments [21,65], and key brain regions involved in emotion processing (e.g. amygdala and VMPFC) are also relevant for moral judgment [15,66,67]. Thus, moral judgment abnormalities in bvFTD patients may also be related to emotion-processing impairments.…”
Section: Discussionmentioning
confidence: 99%
“…The orbitofrontal and ventrolateral prefrontal cortices are implied in the inhibition of automatic or impulsive responses and in processing social prompts [11,12]. The amygdala is involved in moral learning and threat responses [13,14,15]. The precuneus subserves processing of mental states [16] and integration of self-referential stimuli in the broader emotional or moral context of the self [17].…”
Section: Introductionmentioning
confidence: 99%